(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
This paper examines the long-run relationship among Polish, US and Eurocurrency interest rates. There is utilized Johansen’s cointegration technique. The paper employes the three-month and five-year interest rates of Poland, US and Eurocurrency market and tests the weekly versions of these series. The studied period is 01.01.2003 –30.06.2008.The cointegration among Polish, US and Eurocurrency interest rates has not been ex-cluded, with exception of five-year interest rates. The findings indicate strongest cohe-rence of Polish interest rates with Eurocurrency rates than US rates.Throughout this paper, the computations were done with Eviews 5.1.